Perancangan Chatbot Akreditasi UIB Untuk Kemudahan Akreditasi Menggunakan Metode Natural Language Processing - Christian, Yefta; Musfiza, Efelito Hayat; Janata, Adit Afandi; Pratama, Sendi Ari; Fauzi, Muhammad Al; Kurnia, Ahmad Dhani; Eric, Eric (Prodi Sistem Informasi Universitas Dharma Andalas, 2025)
Accreditation is one of the important aspects in ensuring the quality of education in higher education, accreditation assessments are carried out periodically by accreditation institutions. The effectiveness of the accreditation process can be a challenge for Universitas Internasional Batam (UIB) in managing and accessing information related to the required accreditation data quickly. In supporting the accreditation team, a solution is needed that can facilitate the acquisition of information quickly and accurately. The design of a chatbot based on Natural Language Processing (NLP) is considered capable of understanding and responding to questions naturally according to the needs of the accreditation team. This chatbot is designed to provide access in the form of statistical data related to student graduation, lecturer research, and other relevant data related and needed as a consideration for accreditation more efficiently. For this reason, the accreditation chatbot is expected to increase the efficiency of the accreditation team's work and become an innovative solution in managing accreditation information.